Immunomodulation via FGFR inhibition augments FGFR1 targeting T-cell based antitumor immunotherapy for head and neck squamous cell carcinoma. (31st December 2022) - Kono, Michihisa; Komatsuda, Hiroki; Yamaki, Hidekiyo; Kumai, Takumi; Hayashi, Ryusuke; Wakisaka, Risa; Nagato, Toshihiro; Ohkuri, Takayuki; Kosaka, Akemi; Ohara, Kenzo; Kishibe, Kan; Takahara, Miki; et al.
ABSTRACT: Fibroblast growth factor receptor 1 (FGFR1) is overexpressed in multiple types of solid tumors, including head and neck squamous cell carcinoma (HNSCC). Being associated with poor prognosis, FGFR1 is a potential therapeutic target for aggressive tumors. T cell-based cancer immunotherapy has played a central role in novel cancer treatments. However, the potential of antitumor immunotherapy targeting FGFR1 has not been investigated. Here, we showed that FGFR-tyrosine kinase inhibitors (TKIs) augmented antitumor effects of immune checkpoint inhibitors in an HNSCC mouse model and upregulated tumoral MHC class I and MHC class II expression in vivo and in vitro . This upregulation was associated with the mitogen-activated protein kinase signaling pathway, which is a crucial pathway for cancer development through FGFR signaling. Moreover, we identified an FGFR1-derived peptide epitope (FGFR1305-319 ) that could elicit antigen-reactive and multiple HLA-restricted CD4 + T cell responses. These T cells showed direct cytotoxicity against tumor cells that expressed FGFR1. Notably, FGFR-TKIs augmented antitumor effects of FGFR1-reactive T cells against human HNSCC cells. These results indicate that the combination of FGFR-TKIs with immunotherapy, such as an FGFR1-targeting peptide vaccine or immune checkpoint inhibitor, could be a novel and robust immunologic approach for treating patients with FGFR1-expressing cancer cells.